2014
DOI: 10.1186/1471-2164-15-1168
|View full text |Cite
|
Sign up to set email alerts
|

NextGen sequencing reveals short double crossovers contribute disproportionately to genetic diversity in Toxoplasma gondii

Abstract: BackgroundToxoplasma gondii is a widespread protozoan parasite of animals that causes zoonotic disease in humans. Three clonal variants predominate in North America and Europe, while South American strains are genetically diverse, and undergo more frequent recombination. All three northern clonal variants share a monomorphic version of chromosome Ia (ChrIa), which is also found in unrelated, but successful southern lineages. Although this pattern could reflect a selective advantage, it might also arise from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 53 publications
(101 reference statements)
1
31
0
Order By: Relevance
“…With NextGen sequencing, genomes can be completely sequenced to identify all the SNPs in the parents and progeny, yielding many thousands of markers (106). The type 2 × type 10 cross was genotyped using whole-genome sequencing allowing for the identification of recombination breakpoints and short double-crossover events in the progeny (60). Regardless of the density of markers, the limiting factor for linkage mapping is the frequency of crossovers, and this can only be increased by analyzing more progeny.…”
Section: Genetic Mapping In T Gondiimentioning
confidence: 99%
“…With NextGen sequencing, genomes can be completely sequenced to identify all the SNPs in the parents and progeny, yielding many thousands of markers (106). The type 2 × type 10 cross was genotyped using whole-genome sequencing allowing for the identification of recombination breakpoints and short double-crossover events in the progeny (60). Regardless of the density of markers, the limiting factor for linkage mapping is the frequency of crossovers, and this can only be increased by analyzing more progeny.…”
Section: Genetic Mapping In T Gondiimentioning
confidence: 99%
“…1A). The SNF r phenotype was mapped in jQTL as a binary distribution using the ME49-FUDR r ϫ VAND-SNF r genetic map generated previously (39). The primary scan generated one significant peak with a log of odds ratio (LOD) score of 6.57 on chromosome IX between markers MV358 and MV365, corresponding to ME49 region IX:3187822-4202044 (Fig.…”
Section: Mapping Of Snfmentioning
confidence: 99%
“…Quantitative trait locus (QTL) mapping has been used to map the basis of SNF r to chromosome IX (15), although the precise locus responsible has not been identified. A recently described cross between type 2 ME49-FUDR r and type 10 VAND-SNF r parental lines (type 2 ϫ type 10 cross) used the parental strain VAND, which was resistant to sinefungin (39). Importantly, the genomes of the progeny of this cross were sequenced in order to generate a genetic map, which was constructed by identifying single nucleotide polymorphisms (SNPs) inherited from the parents (39).…”
mentioning
confidence: 99%
“…The recent researchers have been shown that T. gondii has unusual population structure with different growth rates [20], frequency of differentiation, motility [21] virulence, persistence, and migration capacity [15,[21][22][23]. Recent developments in molecular tools allow enhancing their success to identify the genetic diversity of the parasite [24,25]. Su et al [25,26] have analyzed the nuclear and plastid genome of 950 isolates from all over word and reported six major clades dividing 15 haplotypes with 138 unique genotypes.…”
Section: Genetic Variation Of Toxoplasma Gondiimentioning
confidence: 99%